Persepsi Mahasiswa Terhadap Pelaksanaan Mini Clinical Examination Excercise (Mini-CEX) Pada Program Pendidikan Kepaniteraan Klinik - Gusti Raditya K; Yoyo Suhoyo; Tridjoko Hadianto (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2012)
Background: Mini-CEX was developed to assess the clinical skills of students through direct observation and constructive feedback on student achievement. To test Mini-CEX well as assessment methods, it is necessary to evaluate the implementation of Mini-CEX as Mini-CEX assessment methods and benefits of the learning process, as well as the professional development of students as future doctors, in the form of assessment of students’ perceptions of the Mini- CEX implementation. The objective of this study are to validate an instrumen for measuring the level of student perceptions in the implementation of Mini-CEX in Faculty of Medicine, Universitas Gadjah Mada’s clerkship program, to know the student’s opinions about the implementation of Mini-CEX as a method of assessment in clerkship program and benefits to student learning and professional development, to know the relationship students’ Mini-CEX point to student’s perception in the implementation of Mini-CEX in clerkship program medical faculty of GMU, and to compare the perceptions of students in Mini-CEX implementation in clerkship program Medical Faculty of GMU based on the characteristics of the department.Method: Research was conducted with a cross sectional study design. The research utilized closed questionnaires, each contained 5 likert scales. The questionnaires were given to the students who conducted clerkship in Faculty of Medicine, Universitas Gadjah Mada during the period of September 2010–March 2011. A total number of 103 students who become subjects in this study, which are consisted of 72 students in Internal Medicine Department and 32 students in Neurology Department. The correlation between student perception and Mini-CEX score was analyzed by using spearman correlation test. Mann-Whitney test was used to analyze the differences student perception between both Departments.Results: Students who are conducting clerkship program in Internal Medicine Department and Neurology Department Faculty of Medicine Universitas Gadjah Mada agree that Mini-CEX can be as assessment and learning tools, and promote the development of student professionalism. Perceptions of students towards the implementation of Mini-CEX in clerkship are not associated with Mini-CEX score. There was no significant difference in students’ perceptions towards the implementation of Mini-CEX between Internal Medicine Department students and Neurology Department students.Conclusion: Students perceived the Mini-CEX to be a practical assessment tool with a positive impact on their learning and professionalism development during clerkship.